Monopole solutions in AdS space - Lugo, Adrián René (2000)
We find monopole solutions for a spontaneously broken SU (2)-Higgs system coupled to gravity in asymptotically anti-de Sitter space. We present new analytic and numerical results discussing, in particular, how the gravitational instability of self-gravitating monopoles depends on the value of the cosmological constant.